Ecology and characteristic of fern - Mohd. Yaman, Maheran (s.n, 2012)
The aim of the research is to explore the potential of fern species as natural indicator to forecast microclimate change in the urban area. Fern also known as pteridophyte are not only valuable in term of its ethno-botanical uses such as food and medicine but also useful in ecological values. Fern can be used to treat unhealthy environment such as absorbing methane gas, fertilizing land and treating heavy metal such as arsenic. Fern also can be used as a potential ecological indicator for microclimate changes. In this research, observation and measurement were made at two different environment which are natural environment; Gunung Jerai, Kedah and Lata Jarum, Pahang and man-made setting environment; Hospital Serdang, Serdang and Secret Garden, Kuala Lumpur.